Ubiquitin ligase RNF123 mediates degradation of heterochromatin protein 1α and β in lamin A/C knock-down cells. - Pankaj Chaturvedi; Richa Khanna; Veena K Parnaik (PLoS ONE, 2012)
The nuclear lamina is a key determinant of nuclear architecture, integrity and functionality in metazoan nuclei. Mutations in the human lamin A gene lead to highly debilitating genetic diseases termed as laminopathies. Expression of lamin A mutations or reduction in levels of endogenous A-type lamins leads to nuclear defects such as abnormal nuclear morphology and disorganization of heterochromatin. This is accompanied by increased proteasomal degradation of certain nuclear proteins such as emerin, nesprin-1α, retinoblastoma protein and heterochromatin protein 1 (HP1). However, the pathways of proteasomal degradation have not been well characterized.To investigate the mechanisms underlying the degradation of HP1 proteins upon lamin misexpression, we analyzed the effects of shRNA-mediated knock-down of lamins A and C in HeLa cells. Cells with reduced levels of expression of lamins A and C exhibited proteasomal degradation of HP1α and HP1β but not HP1γ. Since specific ubiquitin ligases are upregulated in lamin A/C knock-down cells, further studies were carried out with one of these ligases, RNF123, which has a putative HP1-binding motif. Ectopic expression of GFP-tagged RNF123 directly resulted in degradation of HP1α and HP1β. Mutational analysis showed that the canonical HP1-binding pentapeptide motif PXVXL in the N-terminus of RNF123 was required for binding to HP1 proteins and targeting them for degradation. The role of endogenous RNF123 in the degradation of HP1 isoforms was confirmed by RNF123 RNAi experiments. Furthermore, FRAP analysis suggested that HP1β was displaced from chromatin in laminopathic cells.Our data support a role for RNF123 ubiquitin ligase in the degradation of HP1α and HP1β upon lamin A/C knock-down. Hence lamin misexpression can cause degradation of mislocalized proteins involved in key nuclear processes by induction of specific components of the ubiquitin-proteasome system.